Environmental management system according to NBR ISO 14001 in a pulp and paper company (Research, Society and Development, 2020)
Market expansion, product quality improvement, higher production, sustainable development, among others, are some of the possibilities that a company acquired when starting an environmental management system. Much more than taking care of the environment, by implementing a new management, the company becomes more competitive and its product more visible in the market. Qualities are built into the product offered. Producing using quality standards such as ISO 14.001 has been of great importance and a differentiator among global companies. This paper aims to show the advantages that a company has when developing an environmental management system, the new possibilities that the company has after receiving certification of the management implemented and finally this system is exemplified with a pulp and paper company that has a environmental management system in operation. The methodology adopted is indirect documentation, that is, when the work presents a bibliographic review of the theme bringing the latest updates and approaches on the issues presented. It was noticed that companies that already opted to join some movement for the environment had increased their visibility in the market and consequent increase in their sales and growth. Finally, it was evidenced that regardless of the segment that a company fits, when it seeks environmental certification through ISO 14.001, its product gains added value, because this practice exposes the care and concern the company has with the environment.